Health and environment in Brazil: development, territory, and social iniquity - Rigotto, Raquel Maria; Augusto, Lia Giraldo da Silva (Cadernos de saúde pública, 2007)
The present paper deals with the subject of socio-environmental injustice in Brazil as a consequence of the country's current development model in the context of globalization and from the perspective of social struggle. Over time the realization of the development ideology has introduced profound changes in the country's territory, with severe repercussions for population and ecosystem health that have only recently been included on the social agenda. Efforts to reconcile solutions to the social and environmental crises have converged in the concept of sustainable development, within new discourses in the field of collective health (and whose analysis provides the point of departure for this paper). Territory is explored as a useful tool for analyzing the relationship between health, environment, and development, revealing the paradox between Brazil's great natural and human potential and its poverty, reflecting environmental injustice and disregard for human rights. This expanded concept of territorial organization is important for understanding the context of modernization and the possibility for poor populations to enjoy a better life.